(untitled) (MAUSAM, 2003)
In this study the mean daily evapotranspiration (ET) and its contribution in different phases to the total evaporative loss have been worked out for paddy at Nellore. Models have been developed between evapotranspiration/evaporation rates (ET/EP) and number of days from transplanting. ET/EP ratio has been found to reach it peak during the flowering stage in all three seasons. The mean ET/EP ratio is the highest in kharif season. Ratio of evapotranspiration (ET) to total short wave radiation (Rs) has been analysed and the ratio is found to reach its peak value at flowering stage of the crop.